The operator - Harrison, Kim, 1966- (Harrison, Kim, 1966- Peri Reed chronicles., 2016)
"Peri Reed's job eats her mind, but for a special task agent in hiding, forgetting the past can be a blessing. Betrayed by the man she thought she loved and the agency who turned her into the very thing she fought against, Peri abandoned the wealth and privilege of Opti for anonymity riddled with memory gaps and self-doubt. But when a highly addictive drug promises to end her dependency on those who'd use her as a tool for their own success, she must choose to remain broken and vulnerable, or return to the above-the-law power and prestige she once left: strong but without will--for whoever holds her next fix will hold her loyalty. Yet even now as then, a love based on lies of omission might still save her life"--Jacket.